Service quality and students’ satisfaction towards purchasing online educational resources - Rahman, Muhammad Sabbir; Abu Zarim, Zainal (American Research Institute for Policy Development, 2014)
The aim of this research is to explore the degree of influence of the variables:reliability, responsiveness, ease of use and security on the student satisfaction in purchasing online educational resources. A sample of 250 Malaysian and foreign students from different level participated in this inquiry. This research applied descriptive statistics, exploratory factor analysis and structural equation modeling to test the proposed hypothesis. The outcome indicated that security perceived by the respondents were the highest influence on the student satisfaction in purchasing online educational materials. It is indicated that the online sellers of educational materials should concern their effort on raising their services with higher effort to insure the consumer security when they purchase educational materials from online.